Performance of Al2O3/TiO2 hybrid nano-cutting fluid in mql turning operation via RSM approach - Arifuddin, Ariffin; Abd Aziz, Mohammad Redhwan; Wan Hamzah, Wan Azmi; Nurul Nadia, Mohd Zawawi (MDPI, 2022)
Cutting fluids can be used to cool workpieces at high cutting speeds and remove chips from cutting zones. The effectiveness of cutting fluids may be improved with the addition of hybrid nanoparticle dispersion. This study evaluates the effectiveness of an Al2O3-TiO2 hybrid as a cutting fluid in turning operations. The Al2O3-TiO2 hybrid nano-cutting fluid was prepared using a one-step method in computer numerical control (CNC) coolant with concentrations of up to 4%. Utilizing air-assisted nano-cutting fluids injected through a minimum quantity lubrication (MQL) setup, the effectiveness of turning cutting performance, cutting temperature (°C), average surface roughness (Ra), and tool wear (%) were evaluated. Then, the response surface method (RSM) was utilized as the design of experiment (DOE) to optimize the turning cutting performance parameters. The combination of 4% hybrid nano-cutting fluid concentration, 0.1 mm/rev feed rate, and 0.55 mm depth of cut yielded the lowest cutting temperature, surface roughness, and tool wear values of 25.3 °C, 0.480 µm, and 0.0104%, respectively. The 4% concentration of Al2O3/TiO2 hybrid nano-cutting fluid inclusion achieved the highest surface roughness reduction that led to better surface finish and the lowest tool-wear reduction led to longer tool life. Therefore, Al2O3/TiO2 hybrid nano-cutting fluids were strongly recommended in turning operations for CNC lathes.